SIMBOLISASI PERILAKU SEKSDALAM ”DIGITAL PAINTING ART” - AHMAD BAKRI PULUNGAN, Hendra Afriwan, S.Sn., M.Sn., Dr. Yahya, M.Pd (Serupa The Journal of Art Education, 2014)
Sex is the most controversial topics in the community. Most people view sex as something negative. Evensex is considereda taboo anddo not deserve tobe discussed openlywithout anyapparent reason. Sexual Behavior Problemsthe author adopted in the form of digital painting with acontemporary realiststyle. This work dealt with the applicationsusing the application adobephotoshop andillustrator. The purposeof creating the worktoexplainto the public about the dangers, the factors that influence, to determine the characteristics and developmenta lpatterns ofsexual behavior, know the sex behaviorin term soft the health aspects of sexual behavior and visualize symbolizationKata Kunci: Sexual Behavior symbolization, Digital Painting Art